3R Bag / Nor Suhana Sejarta … [et al.] - Sejarta, Nor Suhana; Amran, Nur Fauziah; Nazli, Nur Farzana; Azmi, Arissa Najibah; Roshaheli, Muhammad Wafiq Iman (Faculty of Computer and Mathematical Sciences, 2023)
Responsible Consumption and Production (SDG 12) is one of the 17 Sustainable Development Goals established by the United Nations in 2015. SDG 12 has 11 targets to be achieved at least by 2030. This writing aims to ensure that one of the targets of SDG 12 which by 2030, waste generation can be significantly reduced through prevention, reduction, recycling and reuse. This study was conducted using interview methods, website references and library references. The findings of the study show that uncontrolled consumption and production have resulted in a lot of waste at the global level. Irresponsible human greed leads to environmental damage. In conclusion, the Reduce, Reuse, Recycle (3R) method should be optimized to eradicate global waste and environmental destruction. Be a prudent consumer and producer. When we become smart consumers, we also actually encourage entrepreneurs to be responsible producers.